Improving patient care through nursing: challenges, strategies, and innovations - alzeer, Khawlah nasser; alanazi, Ghadeer Hamoud; Alharbi, Rowan Falah; Albaqami, Reem Mohammed; Alanazi, Shuruq Suhyman; almusabeh, Safia Abdullah; Alruwaili, Daliyah Farhan (Journal of Neonatal Surgery, 2026)
Nursing is a significant element that allows the improvement of the care of patients throughout the health-care continuum, which is achieved by direct clinical care, care coordination, education, and advocacy. As health-care systems become more and more complex, nurses are faced with significant challenges of workforce shortages, burnout, increasing patient acuity, job role ambiguity, and the rapid pace of technological change, all of which have the potential to negatively impact patient outcomes. It is a review of the main issues that interfere with nursing practice and questions evidence-based solutions to it such as optimum staffing, lifelong learning, inter professional collaboration, and patient-centred care models that can be used to enhance care quality and safety. Also, the review outlines the latest advancements in the nursing practice, including health information technologies, telehealth services, and advanced nursing roles, which have enabled the expanded access to care, and increased efficiency and continuity. The review highlights the need of continuous investment in nursing education and leadership and positive policy frameworks, which strengthens the nursing workforce and ensures high-quality, safe, and patient-centred delivery of health-care.